Jobs in global supply chains: a macroeconomic assessment - Takaaki Kizu; Stefan Kühn; Christian Viegelahn (FIW - Research Centre International Economics, 2016)
In its recent World Employment and Social Outlook, the ILO published estimates of the number of jobs related to global supply chains (GSCs) for 40 countries in 1995-2013. This paper provides a detailed description of the methodology that was used for the estimation and documents in more detail global linkages in production, becoming apparent on the labour market. The paper also shows new evidence on the number of jobs supported by different export destinations and analyzes the number of GSC-related jobs in different country groups. In particular, we find evidence for the changing role of China, from a country in which GSC-related jobs are located to a country whose import demand creates these jobs elsewhere. We also show that production linkages between emerging economies create an increasing number of jobs. When focusing on jobs related to manufacturing GSCs, trends in GSC-related jobs reveal the increasing importance of the services sector. Finally, we conduct a sectoral regression analysis and provide evidence that increased GSC participation of a sector as a supplier can be associated with a drop in the wage share.
Keywords: F16; F66; 330